Democratic governance in post-conflict Liberia: An interview with Dr. Amos Swayer - Louise Andersen (Danish Institute for International Studies (DIIS), 2007)
This Working Paper contains an interview with Dr. Amos Sawyer - one of the persons most knowledgeable on Liberian politics and society. Dr. Sawyer presents himself as a Scholar-Activist who is driven equally by the curiosity to understand what is happening and the passion to do something about it. It is from this perspective he speaks on the current situation in Liberia and shares his view on the ongoing post-conflict state-building process. Dr. Sawyer's main claim is that a system of `polycentric governance' is better suited to the social and political realities in Africa's fragile states than the imposed system of unitary sovereignty, which has failed so con-spicuously in Liberia and elsewhere. He discusses the international community's approach to state-building and argues that it is in need of serious rethinking. If the post-conflict order is to be both democratic and sustainable, it must be built from the ground up drawing on internal capabilities and local knowledge. Not on international blue-prints. The ongoing attempts at re-establishing law and order mainly through a strong central government entail a risk of reproducing the basic structural problems that have characterized the Liberian state since its creation.
Keywords: 330; Staatsgründung; Staatsorgan; Demokratisierung; Governance-Ansatz; Liberia